PUBLIC AWARENESS: THE KEY TO IMPROVE CHILDREN ENGLISH READING SKILL - Ainaiyah Shabrina Suciati; Feri Ferdiyanto; Beny Hamdani (LPPM Universitas PGRI Jombang, 2025)
This study aims to analyze the awareness of the community in Bulu village, Kraksaan, towards the importance of English reading skills in children. This research uses qualitative methods with instruments of questionnaires, documentation, and questions involving 10 parents and 15 children in Bulu village. The results of the analysis show that most people understand the importance of English reading skills, but some parents still do not realize the importance of English education in everyday life. In addition, children in Bulu village also lack motivation about the importance of English education due to the lack of support from parents and the surrounding community. Therefore, community awareness is very important to help the development of children English reading skills. This research has implications for the importance of increasing community awareness and support from parents and the surrounding community in improving children's English reading skills.